2011
DOI: 10.1167/iovs.11-7777
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Coagulase Negative Staphylococci (CoNS) Other thanStaphylococcus epidermidisIsolated from Ocular Infections

Abstract: Identification results of these two methods corresponded only in 48.4% of the isolates suggesting that the battery of tests using API were not sufficient enough to identify all the species of CoNS. Therefore, it is sensible to rely on two or more identification methods particularly when API species identification has a lower score. FAFLP genotyping appears to be a reliable and rapid alternative identification method for CoNS that can be used in conjunction with any other phenotypic method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…17 The results exhibited that except for fusidic acid and polypeptide antibiotics, the resistance of Staphylococcus epidermidis to other antibiotics was even higher than that of MRSA, the severity of which should not be ignored as a result. As an opportunistic pathogen, Enterococcus led to increasing infections every year, and its drug resistance has become extremely serious according to the results in our hospital.…”
Section: Discussionmentioning
confidence: 96%
“…17 The results exhibited that except for fusidic acid and polypeptide antibiotics, the resistance of Staphylococcus epidermidis to other antibiotics was even higher than that of MRSA, the severity of which should not be ignored as a result. As an opportunistic pathogen, Enterococcus led to increasing infections every year, and its drug resistance has become extremely serious according to the results in our hospital.…”
Section: Discussionmentioning
confidence: 96%
“…Even commercial identification systems for CoNS such as API STAPH are reported to have problems in identification as exemplified by a study where four isolates which were identified as S. haemolyticus by ITS-PCR were misidentified as S. epidermidis, S. hominis and S. warneri (25,26). Molecular methods, including 16S rDNA based identification is highly reproducible, unambiguous, rapid, accurate and efficient for the epidemiological analysis of medically significant bacteria and also in categorizing them up to species and subspecies level (25). Hence in the current study, identification of the isolates was made by combining the results of biochemical tests, MPCR and 16S rDNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…S. xylosus is a coagulase-negative gram-positive staphylococcal species and a common skin commensal bacterium of humans and other mammals 6 . Some cases of S. xylosus infection, including erythema nodosum 7 , pyelonephritis 8 , and corneal infections 9 occur in humans. In laboratory mice, S. xylosus has been associated with spontaneous dermatitis in both NOS2 −/− mice 10 and athymic nude mice 11 and with conjunctivitis in NADPH oxidase −/− mice 12 , implying that S. xylosus is an opportunistic pathogen.…”
Section: Introductionmentioning
confidence: 99%